Comparative study of mechanical properties of cast and forged Al-3Mg-MnO2 and Al-8Mg-MnO2 composites. Issue 1 (January 2020) - Narain, Vikas; Ray, Subrata
Abstract: The Al-Mg-MnO2 composite is a MnO2 particulate reinforced Al metal matrix composite. Its substantial ductility makes it promising composite for study. The Al-3Mg-MnO2 and Al-8Mg-MnO2 composites were synthesized by stirring 3, 5, and 8 wt% of MnO2 particulates in Al-3Mg melt and Al-8Mg melt to study their mechanical properties. Their microstructure shows intermetallic precipitates of Al, Mg, and Mn at dendrites, grain boundaries and within the grains. In both sets of composites, the hardness, and the yield strength increases with increasing MnO2 content in the cast and forged composites. Both the groups of composites show an increase in tensile strength with increasing particle content from 3 to 5 wt%, a further increase in particle content to 8 wt%, leads to an abrupt decrease in tensile strength in both the group of composites. The percentage elongations in forged composites are lower than those in cast composites, but this decrease is more prominent in Al-8Mg-MnO2 composites in comparison to Al-3Mg-MnO2 composites. The J IC value decreases as the percentage of MnO2 particles increases in Al-3Mg-MnO2 and Al-8Mg-MnO2 composites. Forging increases J IC values in both the class of composites in comparison to their cast counterparts due to work hardening and healing of pores. Crack growth toughness also decreases as the MnO2 particle content increases in Al-3Mg-MnO2 and Al-8Mg-MnO2 composites. Forged Al-3Mg-MnO2 shows decreased T/E ratio in comparison to their cast counterparts except at 8wt%. However, forged Al-8Mg-MnO2 shows improved T/E at 3wt% and a drop at 5wt% and 8wt% MnO2 . Variation of crack growth toughness between cast and forged Al-8Mg-MnO2 is minimal in comparison to that between cast and forged Al-3Mg-MnO2 composites. Abstract : Materials science, Metallurgical engineering, Al-Mg-MnO2 composite, Initial fracture toughness, Growth toughness, Hardness, Elongation, Yield strength, Tensile strength.